2015
DOI: 10.1016/j.acra.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mammographic Technologists on Radiologists' Ability to Interpret Screening Mammograms in Community Practice

Abstract: Purpose To determine whether the mammographic technologist has an effect on the radiologists’ interpretative performance of screening mammography in community practice. Materials and Methods In this institutional review board approved retrospective cohort study, we included Carolina Mammography Registry (CMR) data from 372 radiologists and 356 mammographic technologists from 1994 to 2009 who performed 1,003,276 screening mammograms. Measures of interpretative performance (recall rate, sensitivity, specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In our prior work, we found that technologists do in fact contribute to the observed variability of screening and diagnostic mammography performance. [13, 14] An important factor for mammography performance, specifically sensitivity, is breast positioning during the examination. [15] While the quality of the image is related to both the calibration of the mammography machine and the skill of the technologist, the technologist is ultimately responsible for obtaining correct positioning and sufficient compression to maximize image sharpness.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior work, we found that technologists do in fact contribute to the observed variability of screening and diagnostic mammography performance. [13, 14] An important factor for mammography performance, specifically sensitivity, is breast positioning during the examination. [15] While the quality of the image is related to both the calibration of the mammography machine and the skill of the technologist, the technologist is ultimately responsible for obtaining correct positioning and sufficient compression to maximize image sharpness.…”
Section: Discussionmentioning
confidence: 99%
“…The advanced radiography practitioner is identified as someone who has progressed professionally to a higher level than colleagues through role extension, and has the ability to direct and encourage service delivery within their specialist area. 44 Mammography is a specialist area and in several studies professional growth 21,23e26 and shared responsibility 22,37,38 were mentioned as contributing to deliver high quality service in the chain of early detection of breast cancer. The wording of these descriptions appears to indicate an advanced role for the radiographer.…”
Section: Professional Tasksmentioning
confidence: 99%
“…It strengthens each profession, since in the interprofessional context the uniqueness of each profession becomes more visible. 21,22,26,37,38 Also, work motivation and satisfaction increase when participating in shared decision-making, learning from other health-care professionals, sharing experience, and witnessing the improved quality of care and diagnostics. 22,27,30,34,35 For health-care teams, the benefits of the interprofessional work model include more flexibility in performing tasks, occasional opportunities to replace other professionals for certain tasks, the possibility to give and receive timely feedback, fewer errors and misunderstandings, as well as lower patient recall rate.…”
Section: Efficacy Of Professional Teamworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiology studies have indicated a significant effect in screening results due to variation in mammography technologists, but more research is required to explore what types of variation affect the results. 72 National recommendations suggest that personnel performing sonography have, at a minimum, obtained a national credential in the modality in which they are performing the image acquisition. 73 Utilization of staff performing the imaging who have limited training can reduce sensitivity of disease to 21% to 33% in cardiac valvular abnormalities requiring Doppler evaluation.…”
Section: Requirements Of Facilities Providing a Screening Programmentioning
confidence: 99%